Childhood Adversity and Youth Depression: Influence of Gender and Pubertal Status - Rudolph, Karen D. (2007)
This research examined three possible models to explain how childhood social adversity and recent stress interact to predict depression in youth: stress-sensitization, stress-amplification, and stress-inoculation. Drawing from a stress-sensitization theory of depression, we hypothesized that exposure to childhood adversity, in the form of disruptions in critical interpersonal relationships, would lower youths’ threshold for depressive reactions to recent interpersonal stress. We expected that this pattern of stress sensitization would be most salient for girls negotiating the pubertal transition. These hypotheses were examined in two studies: a longitudinal, questionnaire-based investigation of 399 youth (M age = 11.66 years) and a concurrent, interview-based investigation of 147 youth (M age = 12.39 years). Findings supported the role of stress-sensitization processes in pubertal girls and prepubertal boys, and stress-amplification processes in prepubertal girls. Childhood social adversity specifically predicted sensitization to recent interpersonal, but not noninterpersonal, stress. These findings build on prior theory and research by suggesting that early adversity exerts context-specific effects that vary across gender and development. Future research will need to identify the specific mechanisms underlying this stress-sensitization process.